Hinterland - Lang, Steven, 1951- (University of Queensland Press, 2017)
& lsquo;We have this idea we can live anywhere, that we make a choice, but it's not true. There are places that are for you and places that aren't. You can tell which is which if you're prepared to listen.' Tensions have been slowly building in the old farming district of Winderran. Its rich landscape has attracted a new wave of urban tree-changers and wealthy developers. But traditional loyalties and values are pushed to the brink with the announcement of a controversial dam project. Locals Eugenie and Guy are forced to choose sides, while newcomer Nick discovers there are more sinister forces at work. The personal and the political soon collide in ways that will change their fates and determine the future of the town. In Hinterland, Steven Lang has created a gripping novel that captures contemporary Australia in all of its natural beauty and conflicting ambitions.